Financial Performance of Hospitals in Maine, 1993-2003 - Kane, Nancy (Maine Policy Review, 2004)
Hospitals are the largest single component of healthcare expenditures. Nancy Kane’s study of hospital financial performance fulfills a mandate of Maine’s Dirigo Health Reform Act. By most financial measures, Maine’s hospital industry outperformed hospitals nationwide and in the Northeast during 1993-2003. Still, there is major variability among the state’s hospitals in financial performance. Kane analyzes financial and non-financial characteristics of high-, medium-, and low-performing hospitals, and suggests that not maintaining acute inpatient volume is the biggest problem for low-profitability hospitals. Although no hospital is in imminent danger of failing, Kane suggests a new “blueprint” is needed for Maine’s healthcare system, before financial crisis and loss of access occurs.
Keywords: Maine hospitals; hospital finances